Complicated Complicity, European Collaboration with Nazi Germany during World War II, Edited by Martina Bitunjac and Julius H. Schoeps (Berlin – München - Boston: De Gruyter, De Gruyter-Oldenbourg, 2021), xix + 350 str. (Časopis za suvremenu povijest, 2022)
Prikaz knjige